Malignant Middle Cerebral Artery (MCA) Infarction : How to Manage Now ? - Nakaphan, Sanchai (Thai Journal of Neurological Surgery, 2025)
Background: Malignant middle cerebral artery (MCA) infarction is a devastating clinical entity affecting about 10% of stroke patients. Decompressive craniectomy has been found to reduce mortality rates and improve outcome in patients. Key factors associated with favorable outcome include younger age and early surgical treatment. There is ongoing debate as to whether surgery should be routinely performed, considering the very high rates of disability and functional dependence in elderly survivors. Further data on what is the best management in older age, how to provide the best comprehensive neurological and medical care, and how to inform families facing complex decisions on surgical intervention in deteriorating patients have been still required. Methods: A retrospective case review study was conducted to compare patients treated with medical therapy and decompressive surgery for malignant MCA infarction in Chumphon Ket Udomsakdi Province Hospital over a period of 3 years (from January 2012 and September 2014). Outcome was assessed in terms of mortality rate at 30 days, Glasgow Outcome Score (GOS) on discharge, and modified Rankin scale (mRS) at 6 months. Results: No significant difference was seen between patients treated with medical therapy and decompressive surgery in mortality rate reduction, GOS at discharge, and mRS at 6 months. Mortality rate of medical therapy was 35.7% compared to 30.7% in patients treated with surgery. Good functional outcome based on mRS was seen in 60.8% of patients receiving medical treatment, comparing to 46.2% of patients treated with surgery. Even the results were not met significantly association by statistic calculation, it seem that patients with age > 50 years derived good outcome from medical treatment and the patients with age ≤ 50 years derived better outcome from surgical treatment. Factors associated with good outcome in medical therapy included pre-treated CT midline shift less than 10 mm (P < 0.05) and GCS of 10-13 (P < 0.05). Dominant hemisphere involvement and hemorrhagic transformation were not significantly associated with functional outcome. Conclusion: Malignant MCA infarction is a critical condition that warrant immediate, specialized neurointensive care and often neurosurgical intervention. Early medical therapy should be considered in patients who continue to deteriorate neurologically. Elderly patients may benefit greatly from such an approach, and although disabled, they may be functionally independent. Age is an important factor to consider in patient selection for surgery. Appropriate patients are relatively young, in the first five decades of life.